Analysis of community willingness to pay for water environmental services in Wan Abdul Rachman Grand Forest Park - Nabila Daud; Christine Wulandari; Pitojo Budiono; Eny Puspasari (Global Forest Journal, 2025)
Wan Abdul Rachman Grand Forest Park (Tahura WAR) is a conservation forestarea that serves as a source of water resources that the community utilizes daily.This research analyzes the characteristics influencing people's willingness to payfor water environmental services in the Tahura WAR. This research wasconducted from October to November 2024. The research location is based onboth villages, where water users are from the Tahura WAR area. Based on thisresearch, the results obtained show that the characteristics of respondents' age,occupation, income, water source, and the amount of water demand/day positivelyinfluence the willingness to pay of the community. The variable that has asignificant influence is income. In contrast, the variables of age, occupation, watersource, and the number of water needs/day do not significantly influence the valueof the willingness of the community of water environmental service users in WanAbdul Rachman Forest Park. This research is expected to make a scientificcontribution to developing studies on environmental economics, especially in thecontext of willingness to pay for water environmental services. The results of thisstudy are expected to be a reference for future researchers who are examiningsocial, economic, and environmental factors